2018
DOI: 10.1016/j.oceaneng.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Mooring system fatigue analysis for a semi-submersible

Abstract: T-N curves, S-N curves, and fracture mechanics (FM) based mooring system fatigue analyses for a semisubmersible are presented. Stress ranges are calculated based on the tension ranges of mooring lines subjected to the combined loading process induced by the motions of wave frequency (WF) and low frequency (LF). A comparison between T-N curves, S-N curves, and FM based mooring fatigue analyses for the semi-submersible is made and the results show that the fatigue lives predicted by the three approaches Page 2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is equipped with three mooring lines, spread 120° apart, as depicted in Figure 1. The nonlinear time-domain motion equations, as regards the global reference system with origin on the projection of the FOWT centre of mass on the waterplane area, are provided by Equation (1), which represents the commonly embodied hydrodynamic model for FOWTs [31][32][33]:…”
Section: Model Description Of Dynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is equipped with three mooring lines, spread 120° apart, as depicted in Figure 1. The nonlinear time-domain motion equations, as regards the global reference system with origin on the projection of the FOWT centre of mass on the waterplane area, are provided by Equation (1), which represents the commonly embodied hydrodynamic model for FOWTs [31][32][33]:…”
Section: Model Description Of Dynamic Analysismentioning
confidence: 99%
“…The reliability of long-term mooring systems for floating offshore wind turbines (FOWTs), deployed on intermediate and deep-water depth, is a key factor to move the offshore wind energy sector towards the commercialization phase, provided that in the last two decades several accidents, mainly due to mooring failures, occurred throughout the world [1]. Indeed, one of the expected goals of the Horizon 2020 "Secure, clean and efficient energy" work programme [2] is the development of reliable, sustainable and cost-efficient mooring systems for FOWTs, with the main aim of making the offshore wind energy sector more competitive on the international market, as regards other well-established renewable sources.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations results have been validated by the laboratory test in which the environmental incidence directions are the same. Thus, in the following study, the environmental loads are assumed in the same incidence direction following the literature 49 and a total of eight directions are observed and considered. The performance of RBFNN using environmental parameters to predict the extreme tension of mooring lines is assessed and presented in Figure 10.…”
Section: Case Studymentioning
confidence: 99%
“…Nijssen (2006) proved that the computational effort of the fracture mechanics approach is not justified by the small advantage over the Palmgren-Miner rule approach. Xue et al (2018) concluded that, if appropriate safety factors as suggested by DNVGL-OS-E301 are considered with the S-N curve method, the two methodologies are generally comparable in terms of predicting the fatigue life. In the present study, the S-N curve approach was employed to estimate the fatigue damage rate and predict the fatigue life of mooring lines.…”
Section: Fatigue Analysismentioning
confidence: 99%
“…They also showed that increasing the analysis duration did not considerably change the results of the fatigue analysis. Xue et al (2018) analyzed the fatigue behavior of the mooring system for a semisubmersible. They compared different fatigue evaluation methods and found that the T-N curve approach is much more conservative than the S-N curve approach.…”
Section: Introductionmentioning
confidence: 99%